Blossoming of Romance Language Literature Translations During the Era of Croatian Second Moderna: Translations of Spanish Literature in the Journal Krugovi - Knežević, Sanja (Przekłady Literatur Słowiańskich, 2024)
Poets of second wave modernism in Croatian literature, and especially the generation of Krugovi journal poets, open up through translations from other literatures. There has been much talk about the importance of Anglo-Saxon translations penned by Antun Šoljan, Ivan Slamnig, and others, but it is also the generation that opened up to translations of Romance literatures. Translations from Romance literatures (especially Italian literature, and to a lesser extent Spanish) were viewed, due to post-war ideological and political circumstances, as somewhat subversive. However, with the appearance of the journal Krugovi (1952), translations of Italian, Spanish, and French literature experience a new boom. In this paper, I will examine the translation work of poet and editor of Krugovi, Nikola Milićević, and his translations of Spanish poets.